Obama campaign: an insider's view. Issue 4 (7th March 2013) - Muir, David; Axelrod, David
Abstract : After the 2010 mid term elections, President Obama's chances of re‐election look bleak. Here, one of Obama's key political strategists, explains how Obama was able to achieve victory in 2012.David Axelrod gives away some 'tricks of the trade' and allows a glimpse inside one of recent history's most successful electoral machines.